2005
DOI: 10.3390/10010201
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dearomatization of Phenols and Anilines via λ3- and λ5-Iodane-Mediated Phenylation and Oxygenation

Abstract: Treatment of 2-methylphenols with chloro(diphenyl)-λ3-iodane led to their regioselective dearomatizing 2-phenylation into cyclohexa-2,4-dienone derivatives via a proposed ligand coupling reaction. In the same vein of investigation, treatment of 2-methylanilines with the λ5-iodane 2-iodoxybenzoic acid IBX reagent led to their regioselective dearomatization into previously undescribed ortho-quinol imines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 56 publications
0
33
1
1
Order By: Relevance
“…The 1 H NMR and 13 C NMR of 21 agreed with those reported in literature. 42,43 Synthesis of 1,2,4-Trimethyl-6-oxocyclohexa-2,4-dien-1-yl 2,2,2-trichloroacetimidate (22) and 5,7,7a-Trimethyl-2-(trichloromethyl)-3a,7a-dihydrobenzo[d]oxazol-3a-ol (23). To a suspension of sodium hydride (∼27 mg, 1.05 mmol, 95% w/w) in dry THF (3 mL) was added a solution of starting alcohol 21 (200 mg, 1.32 mmol) in dry THF (2 mL) at −20°C, and the mixture was allowed to stir at −20°C for about 30 min.…”
Section: ■ Conclusionmentioning
confidence: 98%
See 2 more Smart Citations
“…The 1 H NMR and 13 C NMR of 21 agreed with those reported in literature. 42,43 Synthesis of 1,2,4-Trimethyl-6-oxocyclohexa-2,4-dien-1-yl 2,2,2-trichloroacetimidate (22) and 5,7,7a-Trimethyl-2-(trichloromethyl)-3a,7a-dihydrobenzo[d]oxazol-3a-ol (23). To a suspension of sodium hydride (∼27 mg, 1.05 mmol, 95% w/w) in dry THF (3 mL) was added a solution of starting alcohol 21 (200 mg, 1.32 mmol) in dry THF (2 mL) at −20°C, and the mixture was allowed to stir at −20°C for about 30 min.…”
Section: ■ Conclusionmentioning
confidence: 98%
“…The [4 + 2]-Diels−Alder dimerization can be blocked merely by introducing a small alkyl or alkoxy substituent to the C-5 position of the 2,4-cyclohexadienone system. 42,43 Oxidative dearomatization of 2,3,5-trimethylphenol has been reported using SIBX as the oxidant, albeit in only 12% isolated yield of the desired alcohol 21. 43 The hydroxytrimethylcyclohexadienone 21 has also been prepared in modest (35%) yield by periodate oxidation.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…47) Oxidation with oiodylbenzoic acid (IBX) also occurred at the ortho position, reported respectively by Pettus' group 48) and Quideau's group. 49,50) These results strongly suggested that a trivalent iodine species is generated in situ by 3 and Oxone ® , it then oxidizes the phenols to produce p-quinols. Many reports in the literature have described oxidation of iodoarene with Oxone ® to give iodine(V) compound.…”
mentioning
confidence: 85%
“…Zwar ist berichtet, dass Iodbenzol durch Persäuren zu Iodoxybenzol oxidiert wird; [181] o-Iodbenzoesäure wird allerdings typischerweise nur bis zur Oxidationsstufe von o-Iodosylbenzoesäure (IBA) oxidiert. [40c, 182] Die Dearomatisierung von anderen aromatischen Systemen wie Anilinen [183] und Indolen [184] gelingt ebenfalls bei Verwendung von IBX. Porco et al zeigten, dass auch 2-Benzopyriliumsalze wie 146 durch IBX in 1,2-Dichlorethan-(DCE)/TFA oxidiert werden (Schema 48).…”
Section: Oxidation Von Phenolenunclassified